2023
DOI: 10.1021/acs.cgd.3c00016
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable and Insensitive Energetic Cocrystals Comprising Nitrobarbituric Acid Coformers

Abstract: Four novel energetic cocrystals of 5-nitropyrimidine-2,4,6(1H,3H,5H)-trione/nitro barbituric acid (NBA) with energetic coformers 1H-tetrazol-5-amine (AmTz), 5-(4-nitro-1H-pyrazol-3-yl)-4H-1,2,4-triazol-3-amine (NPTA), 1,3-diaminoguanidinehydrochloride (DAG), and 7H-[1,2,4]triazolo[4,3-b][1,2,4]triazole-3,6,7-triamine (TATOT) were synthesized for the first time and confirmed by single-crystal X-ray diffraction. Three cocrystals, NBA:AmTz, NBA:NPTA, and NBA:DAG, were obtained in a stoichiometry of 1:1, while NBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The H···H interactions with 17% contribution stabilize the interactions in the crystal. It is shown that each of the H···H contacts stabilizes the molecule by increasing its energy by up to 10 kcal mol –1 rather than suggesting the presence of nonbonded steric clashes . The mechanical insensitivity to impact and friction (IS > 40 J, and FS = 360 N) in GDNM is caused by the strong intra- and intermolecular close contacts of the O···H and N···H (64%) interactions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The H···H interactions with 17% contribution stabilize the interactions in the crystal. It is shown that each of the H···H contacts stabilizes the molecule by increasing its energy by up to 10 kcal mol –1 rather than suggesting the presence of nonbonded steric clashes . The mechanical insensitivity to impact and friction (IS > 40 J, and FS = 360 N) in GDNM is caused by the strong intra- and intermolecular close contacts of the O···H and N···H (64%) interactions.…”
Section: Resultsmentioning
confidence: 97%
“…These molecules consist of an energetic framework substituted with certain explosophoric groups (−N 3 , −NO 2 , −ONO 2 , −NHNO 2 , etc. ). These days, the research is moving toward structural design, synthesis, and property optimization, as well as application development, together with the growing focus on safety and accessibility of energetic materials. Researchers are constantly looking for novel, relatively safe energetic molecules that possess a high stored energy. The nitro-substituted methanides such as nitromethane, dinitromethane, trinitromethane, and tetranitromethane, as well as their derivatives, are crucial ingredients and intermediates in HEDMs. , However, most of them are often unstable and easily detonate through heat or impact, which restricts their applicability for defense and civilian fields in larger quantities.…”
Section: Introductionmentioning
confidence: 99%
“…aOnset decomposition temperature (DSC, 10 °C min −1 ).bPycnometer density at 25 °C.cCrystal density.dHeat of formation.eDetonation pressure.fDetonation velocity.gImpact sensitivity.hFriction sensitivity.iDehydration temperature.jDecomposition temperature.kRef. 26.lRef. 23.…”
Section: Resultsmentioning
confidence: 99%
“…High energy density materials (such as explosives, propellants, and pyrotechnics) have been used for centuries in military and civilian applications [1][2][3][4][5]. In recent years, there has been a great deal of interest in the synthesis of nitrogen-rich energetic materials in an efficient way [6][7][8]. High energy output is always a priority for newly developed compounds, but sensitivity to unintended stimuli has redirected attention to the molecular stability and safety of energetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of various explosophoric groups such as nitro (-NO 2 ), nitramine (-NHNO 2 ), azide (-N 3 ), etc., on a particular heterocyclic framework is a widely used and effective strategy to boost the detonation performance of the compounds [19][20][21][22]. To address the ongoing demands for stable energetic materials with better performance, 1,2,3-triazoles, 1,3,5-triazines, pyrazoles, and imidazole have drawn much interest among other heterocyclic frameworks [23][24][25][26][27]. Energetic compounds with symmetric and asymmetric C-C bond combinations of heterocyclic backbones with five-membered rings are much explored in the literature [14,24], while the combination of six and five-membered C-C Abhishek Kumar Yadav and Manojkumar Jujam contributed equally.…”
Section: Introductionmentioning
confidence: 99%